ANALISIS SISTEM ANTRIAN UNTUK PENGOPTIMALAN PELAYANAN TELLER PADA PT BANK CENTRAL ASIA Tbk. SRAGEN - Putri Puspita Sari; Erni Widajanti; Sunarso Sunarso (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2020)
The purpose of this study are to obtain a quening system model, and obtain the results analysis on the queuing system in PT Bank Central Asia Tbk. Sragen. The data used in this study are quantitative data in the form of time used in service. Data collection is done by direct survey and obsevation method in the ticket window PT Bank Central Asia Tbk. Sragen. This research uses a Leddy formulawith a sample of 100 customers. This research uses analysis techniques Single Channel Single Phase and Multi Channel Single Phase.Test results show the performace of the teller service queuingsystem in the PT Bank Central Asia Tbk. Sragen is in accordance with procedures and the teller service using the queuing system in the PT Bank Central Asia Tbk. Sragen is optimal.